Risk Preferences and Training Investments - Marco Caliendo; Deborah A. Cobb-Clark; Cosima Obst; Arne Uhlendorff (Institute of Labor Economics (IZA), 2020)
We analyze workers' risk preferences and training investments. Our conceptual frame- work differentiates between the investment risk and insurance mechanisms underpin- ning training decisions. Investment risk leads risk-averse workers to train less; they undertake more training if it insures them against future losses. We use the German Socio-Economic Panel (SOEP) to demonstrate that risk affinity is associated with more training, implying that, on average, investment risks dominate the insurance benefits of training. Crucially, this relationship is evident only for general training; there is no relationship between risk attitudes and specific training. Thus, as expected, risk preferences matter more when skills are transferable – and workers have a vested interest in training outcomes – than when they are not. Finally, we provide evidence that the insurance benefits of training are concentrated among workers with uncertain employment relationships or limited access to public insurance schemes.
Keywords: J24; C23; D81; 330; human capital investment; work-related training; risk preferences